Comparative Analysis of Integrated Crop Management (ICM) Implementation on Hybrid Maize Production and Farmers’ Income (Zea mays L.) - Dinar Dinar; Ida Marina; Milla Syamsiah; Sri Umyati; Dety Sukmawati (Jurnal Penelitian Pendidikan IPA, 2026)
Hybrid maize (Zea mays L.) is one of the strategic commodities in Indonesia that plays an important role in supporting national food security and farmers’ income. One of the technologies introduced to improve maize productivity is Integrated Crop Management (ICM), which integrates several agronomic practices such as the use of improved varieties, optimal plant population, balanced fertilization, and integrated pest management. However, the level of ICM adoption among farmers is still varied, which may affect production performance and farm income. This study aimed to evaluate the implementation of Integrated Crop Management (ICM) technology and to compare the production and income of hybrid maize farmers who implement ICM technology and those who do not. The research used a quantitative survey approach involving hybrid maize farmers as respondents. Data was collected through field observations, interviews, and farm records. The results showed that the implementation of ICM technology significantly improved hybrid maize production and farmers’ income. Farmers implementing ICM technology achieved an average income of IDR 6,247,824 per hectare per planting season, while farmers applying non-ICM practices earned IDR 2,475,494 per hectare per planting season. The higher income was mainly driven by better crop management practices, including optimal plant population, balanced fertilization, and integrated pest management. These findings indicate that Integrated Crop Management technology contributes to improving production efficiency and farm profitability. Therefore, strengthening the dissemination and adoption of ICM technology is important to enhance the sustainability of hybrid maize farming systems